Struktur dan komunitas tanaman pekarangan di desa Jabon Mekar, Kecamatan Parung, Bogor - Budi Prasetyo; Dede Setiadi; Eko B. Walujo (The Ethnobiological Society of Indonesia, 2005)
Jabon Mekar village is well-known as the central of fruit producing. Many kinds of fruit are planted and developed in this area. It is estimated as a buffer zone of Jakarta and subject of the urban development. The aim of the research is to study the community structure and vegetation profile of home-garden system in the village of jabon Mekar. The research was located at Jabon Mekar village, subdistrict of Parung, Bogor regency. The methods used for vegetation analysis were the quadrate method to find density, frequency, dominance, and important index value of plant species. The result of the research found 311 species of plants from 245 genus, 86 families and 36 cultivars. The plants were grouped into 6 categories i.e. the group of miscellaneous plants, ornamental plants, fruit plants, vegetable plants, tradionally medicinal plants, and food plants. The highest value of density of plant species for all group plants based on function found at the home-garden 400 m2 width types and then followed by home-garden of 1200 m2, 800 m2, and 2000 m2 width types. The all group of plants based on function in every types of widen home-garden have a tendency not to spread. The highest relative frequency was the group of fruit plants followed by the group of ornamental, miscellaneous, traditionally medicinal, vegetable and food plants. While the highest value of relative dominance is the group of miscellaneous plants, and then followed by ornamental plants, fruit plants, vegetable plants, tradionally medicinal plants, and food plants. The diversity of plant species at home-garden was at the high level. At the all of the widen homegarden type, the research noted that there were 57 species of fruit plants and dominated by Musa spp. It is also noted that 105 species of ornamental plants dominated by Acalypha sinensis, and in the 48 species of traditionally medicinal plants is dominated by _Ageratum houstonianum. While in the 15 species of vegetable plants is dominated by Gnaw& gaemon. And in the 7 rpecies of food plants is dominated Manihot eseulenta. Finally, in the 79 species of misceliadeous gro,ip of plants is dominated by Polytrias amaura.